2016
DOI: 10.4238/gmr.15017720
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference house­keeping genes in the J774A1 macrophage cell line for quantitative real-time PCR

Abstract: ABSTRACT.Macrophages are essential components of the innate and adaptive immune responses, playing a decisive role in atherosclerosis, asthma, obesity, and cancer. The differential gene expression resulting from adhesion of macrophages to the extra-cellular matrix (ECM) has been studied in the J774A1 murine macrophage cell line using quantitative polymerase chain reaction (qPCR). The goal of this study was to identify housekeeping genes (HKGs) that remain stable and unaltered under normal culture conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Quantitative PCR was conducted with SYBR Premix EX Taq under the conditions suggested by the manufacturer (Life Technologies). The quantity of respective genes was calculated by the comparative Ct method with glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) used as an internal reference (Ferraz & Fernandez, ).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative PCR was conducted with SYBR Premix EX Taq under the conditions suggested by the manufacturer (Life Technologies). The quantity of respective genes was calculated by the comparative Ct method with glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) used as an internal reference (Ferraz & Fernandez, ).…”
Section: Methodsmentioning
confidence: 99%
“…Only few studies reported results of gene expression in monocytes/macrophages in sepsis experimental approaches ( Table 1). The authors mostly performed in vitro studies using mice bone marrow-derived monocytes/macrophages [18,22], J774A1 murine macrophage cell line [23], monocytes from healthy donors stimulated with LPS [24] and monocytes from patients with relapsing-remitting multiple sclerosis [25]. It is notable the lack of study in monocytes/macrophages from septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…qPCR is one of the most sensitive method to evaluate the expression level of genes of interest under different experimental conditions, and thus in order to obtain reliable results it is crucial to select the suitable reference genes [ 26 , 29 34 ].…”
Section: Discussionmentioning
confidence: 99%